Multiplier Effect of Incentive Policy and Ease of Investment on the Welfare of the People (Study in Bangka Belitung Islands Province During The 2010 – 2021 Period) - Arkum, Darol; Amar, Hattami (Journal of Management Economic and Financial, 2025)
Abstract Improving the standard of living requires active government intervention, often in the form of policies aimed at encouraging domestic and foreign capital investment. This study aims to analyze the multiplier effect of incentive and investment facilitation policies on the well-being of residents in the Bangka Belitung Islands Province. Specifically, it examines the impact of these policies on key socio-economic indicators, including the Human Development Index (HDI), regional GDP, unemployment rate, poverty rate, and income inequality. This research employs descriptive and correlational quantitative methods, utilizing a multiple linear regression model to analyze the relationship between foreign and domestic investment (independent variables) and socio-economic indicators (dependent variables). The data used were sourced from the Central Office of Public Prosperity, statistical agencies, and other relevant institutions. The findings reveal that incentive and investment facilitation policies directly increase the value of investments, which positively and significantly impacts regional GDP and the Human Development Index. Furthermore, investment growth is associated with a reduction in poverty levels and income inequality. However, increased investment does not significantly affect the unemployment rate. These results suggest that while investment policies are effective in improving several key indicators, their impact on job creation requires further consideration. These findings underscore the importance of government oversight in ensuring that investors comply with regulations, adopt labor-intensive strategies, and prioritize the use of local labor. By doing so, central and local governments can achieve both short-term and long-term development goals, fostering inclusive economic growth and reducing disparities.